IMPLEMENTASI PERATURAN MENTERI PERHUBUNGAN REPUBLIK INDONESIA NOMOR 10 TAHUN 2012 TENTANG STANDAR PELAYANAN MINIMAL ANGKUTAN MASSAL BERBASIS JALAN (STUDI KASUS PROGRAM TRANS METRO PEKANBARU TAHUN 2012-2013) - Robby Setiawan; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Regulation of the Minister of Transport of the Republic of Indonesia Number 10 Year 2012 on Minimum Service Standards -Based Bulk Road Transport regulates the minimum service standards that should be applied in the implementation of a mass public transport system based on the way each region . Standard services may include security , safety , comfort , affordability , equality and regularity . The purpose of this study was to determine the factors that affect the implementation process of the Minister of Transport of the Republic of Indonesia Regulation No. 10 Year 2012 on Minimum Standards of Road Transport Based on Mass Trans Metro Pekanbaru program 2012-2013 . Location of the study was conducted in the Department of Communication and Information Pekanbaru . This research is descriptive qualitative research method . The nature of this research is a case study . The results showed that the implementation of the Regulation of the Minister of Transport of the Republic of Indonesia Number 10 Year 2012 on Minimum Service Standards -Based Bulk Road Transport can not run optimally . Several factors are influencing policy measures , financial resources , human resources , time resources , the characteristics of the implementing agency , the attitude trends , communication between the implementing organization and activist , social environment , economic environment , political environmentKeywords : Implementation of policy , Minimum Service Standards -Based Bulk Road Transport , Trans Metro Pekanbaru Program